Managing libraries for effective services in Nigerian schools (2004)
This paper discusses how school libraries can be managed so that effective library services will be rendered in Nigerian primary and secondary schools. It views management from the process perspective and identified planning, organizing, staffing, controlling and directing as the management functions which the heads of school libraries have to perform so that effective services can be rendered. The paper also submits that the quality of library services depends on the level of performance of the chief executive of school libraries. It recommends formal training in both management and librarianship for school librarians so that they can perform well in their duties; the allocation of a percentage of the school subvention for the development of school libraries and the employment of only professionally qualified librarians in school libraries.